Exploring challenges in Giardia cyst visualisation by common microscopy methods - Natália de Melo Nasser Fava; Kamila Jessie Sammarro Silva; Bárbara Luíza Souza Freitas; Maria Júlia Rodrigues da Cunha; Valdinei Luís Belini; James Stephen Gerard Dooley; Pilar Fernandez-Ibañez; John Anthony Byrne; Lyda Patricia Sabogal-Paz (Water Practice and Technology, 2023)
Giardia spp. is an intestinal parasite responsible for worldwide disease outbreaks. Guiding researchers and practitioners to choose among current methods for microscopy detection of the infectious forms may be directly beneficial to public health and the environment. This study provides an overall comparison of brightfield (BF), fluorescence and darkfield (DF) microscopies for detecting Giardia duodenalis and Giardia muris cysts, by illustrating micrographs of such protocols applied to purified samples, as well as discussing advantages and constraints based on secondary information and collected data. BF analysis included Lugol's iodine staining. In fluorescence microscopy, samples were processed by immunofluorescence assay (IFA) with DAPI and by standalone DAPI dye. Cyst suspensions were also analysed by DF microscopy using a recently developed low-cost system. The three techniques enabled detecting Giardia spp. cysts, although they did not provide species identification by morphology. The overview of each method points out some relevant aspects to consider when selecting common optical microscopy techniques, and includes challenges and advantages regarding each of them. HIGHLIGHTS Comparisons of BF, DF, standalone DAPI and IFA-combined are provided.; BF and DF may be alternatives for low-cost detection of Giardia cysts.; Combinations of at least two diagnostic methods are recommended to minimise inherent errors.;